PRE-SERVICE ENGLISH TEACHER’S PERCEPTION ON COLLABORATIVE GENRE-BASED WRITING (Universitas Negeri Semarang, 2015)
This study was aimed at investigating the collaborative learning effectiveness and contribution toward pre-service English teachers’ (PSETs’) perception conveyed on genre-based writing lectures. The sample was 86 undergraduate pre-service English teachers (PSETs), Tidar University of Magelang (45 respondents) and Widya Dharma University of Klaten (41 respondents). This study used simple random sampling. Data were collected by means of questionnaire using 5-scaled Likert rating to obtain PSETs’ perception, and then analyzed quantitatively by applying the SPSS program. The findings showed that the highest response toward each category in the perception referred to (1) 41.9% or 36 responses on sometimes toward lecturer’s instruction method; 44.2% or 38 responses on seldom toward learning assessment process; 48.2 or 41 responses on seldom toward lecturer’s assessment mechanism; and 53.5% or 46 responses on sometimes toward lecturer’s instruction evaluation and reflection; and (2) there were 47.4% or 45 responses on sometimes which ranked to the highest response level on group’s performance goals; 48.4% or 46 responses on seldom which engaged PSET’s interpersonal competence; 48.4% or 46 responses on frequent which guided group maintenance; and 41.1% or 39 responses on sometimes toward classroom work.